SOIL PHYSICAL PROPERTIES AND DEVELOPMENT OF COTTON CROP IN NO-TILLAGE SYSTEM - Ferrari, S.; Furlani Junior, E.; Ferrari, J.V.; Vargas, P.F.; Montanari, R.; Persegil, E.O.; dos Reis, A.R. (Revista Brasileira de Engenharia de Biossistemas, 2014)
This study aimed to evaluate the effect of cover crops on changes in soil physical properties and cotton plant growth related to no-tillage system and pre-sowing nitrogen application in cotton crop. The experimental design was a randomized blocks design composed of: three cover crops (forage turnip, black oat and white oat) sowing at winter period; four nitrogen rates (0, 30, 60, and 90 kg ha-1 of N). In this study, penetration resistance, gravimetric moisture, plants height and plants nodes of cotton crop were evaluated. The use of black oats provided increased surface soil moisture while the forage turnip provided increased moisture at depth. The use of cover crops did not alter the penetration resistance. The use of increasing nitrogen rates in pre sowing of cotton crop provided increase in plant height and number of nodes per plant.